Sentence Comprehension and Its Association with Executive Functions in Patients with Parkinson's Disease - Katrien S. F. Colman; Janneke Koerts; Laurie A. Stowe; Klaus L. Leenders; Roelien Bastiaanse (Parkinson's Disease)
Coexistent impairments in executive functions and language comprehension in patients with Parkinson's disease (PD) have been repeatedly observed. In this study, the aim was to provide insights into the interaction between linguistic representation and processing and executive functioning. Therefore, sentence comprehension and executive functions were assessed in 28 Dutch-speaking PD patients and 28 healthy control subjects. Three aspects of the sentence materials were varied: (1) phrase structure complexity, (2) sentence length, and (3) picture congruence. PD patients with mild-to-moderate disease severity showed decreased sentence comprehension compared to healthy control subjects. The difficulties encountered by PD patients were not limited to one aspect of the sentence materials. The same pattern of results was present in healthy control subjects. Deficits in set-switching were specifically associated with the comprehension of passive sentences. Generally, our study confirms that there does not appear to be a language faculty encapsulated from the influence of executive functions.